Stratified mass selection, individual selection between and within, and genetic gains in native maize varieties - Joaes Alves da Silva Pereira; Vanderley Borges dos Santos (Revista Ceres)
ABSTRACT Maize is an important cereal that is grown and consumed all over the world. Among the selection methods that contribute to increasing the frequency of favorable alleles in native maize populations, selection between and within and stratified mass selection in half-sibling families has proven efficient. This study aimed to conduct an individual selection between and within and stratified mass selection in ten half-sibling families of native maize and to estimate the variance components, genetic parameters, and selection gains for them. Ten half-brother families of families were evaluated. The experimental design was DBC, with two replications totaling 20 experimental units, evaluating four plants per plot. The spacing used was 0.8 by 0.3 m. The following were evaluated: stalk diameter (SD), ear length (EL), ear diameter (ED), number of rows (NF), number of grains per row (NGR), ear mass (EM), and total grain mass (TGM) were evaluated. Individual analyses were carried out for all the traits evaluated, selected to increase the original means with a selection intensity of 50% between/50% within. Stratified mass selection yielded higher selection gains than selection between and within families. The selection of the character’s ear mass and total grain mass showed the highest estimates of genetic gain, 54.45 and 48.37%, respectively.